Pyrolysis of hydrochar from digestate: Effect of hydrothermal carbonization and pyrolysis temperatures on pyrochar formation. (November 2016) - Garlapalli, Ravinder K.; Wirth, Benjamin; Reza, M. Toufiq
Graphical abstract: Highlights: Digestate was hydrothermally carbonized at 180, 220, and 260 °C. Hydrochar was pyrolyzed at 400, 600, and 800 °C. Pyro-HTC char has much higher surface area than hydrochar. Pyrolysis of hydrochar reduces the PAH content in the pyro-HTC char. Abstract: Digestate from anaerobic digestion of biomass often contains more than 90% of water, which is economically unfavorable for pyrolysis. Hydrothermal carbonization (HTC) has potential to treat very wet biomass, however, the hydrochar may be acidic, contains polycyclic aromatic hydrocarbons (PAH) and toxic organic substances (e.g., phenolic compounds), and has very low Brunauer-Emmett-Teller (BET) surface area. In this study, pyrolysis of digestate derived hydrochar is performed at various pyrolysis and HTC temperatures. Solid chars were characterized for elemental analysis, pH, PAH, BET, pore size and volume, and phenolic substances, while HTC process liquids were characterized for pH, organic acids, furfural derivatives, and phenolic substances. Physicochemical characteristics of pyro-HTC char were compared with corresponding pyrochar and hydrochar. Pyro-HTC chars produced at higher HTC (i.e., 260 °C) and pyrolysis temperatures (i.e., 800 °C) showed highest BET surface area (63.5 m 2 g −1 ), no PAH, relatively mild basic pH (9.34), and no phenolic compounds.